The Impact of Decentralization on Local Governance: Comparative Study between Java and Sulawesi - Syakir, Irvandy; Elbina, Elsa (Moccasin Journal De Public Perspective, 2025)
Decentralization has been a central pillar of governance reform in Indonesia, aiming to redistribute political authority, administrative functions, and fiscal resources from the central to local governments. This study examines the impact of decentralization on local governance through a comparative qualitative analysis of two contrasting regions, Java and Sulawesi. Case studies were conducted in Surabaya and Yogyakarta representing Java, and Makassar and Gorontalo representing Sulawesi. Data were gathered from in-depth interviews and secondary sources, with particular attention to administrative capacity, fiscal autonomy, and citizen participation. The findings reveal marked regional disparities in decentralization outcomes. In Java, decentralization has contributed to more effective governance, supported by stronger institutions, greater fiscal independence, and active citizen engagement, as reflected in Surabaya’s digital governance initiatives and Yogyakarta’s participatory planning model. In contrast, decentralization in Sulawesi remains constrained by weak institutional capacity, heavy dependence on central government transfers, and political fragmentation. These conditions limit the effectiveness of local governance and policy implementation. This study underscores that decentralization does not function uniformly across regions but is shaped by variations in institutional strength and fiscal capacity. It highlights the need for targeted capacity-building and fiscal reforms in less-developed regions to ensure more equitable decentralization outcomes.